Handbook of child and adolescent anxiety disorders - McKay, Dean; Storch, Eric A. (Springer eBooks., 2011)
Is it school refusal or separation anxiety disorder? Can preschoolers have panic attacks? Does food neophobia really exist? For readers seeking ways to improve assessment, case conceptualization, or treatment plans as well as a more general understanding of anxiety disorders among children, the Handbook of Child and Adolescent Anxiety Disorders addresses these and many other complex issues. A straightforward companion to the diagnostic manuals, this volume crosses theoretical boundaries to describe in depth the wide range of children?s anxiety disorders and to explain the developmental nuances that separate them from their adult analogues. Coverage includes: Diagnostic and etiological models of children's anxiety disorders (i.e., genetic, cognitive-behavioral, taxonomic, neuropsychological, dimensional). Differential diagnosis guidelines for generalized anxiety disorder (GAD), phobic conditions, obsessive-compulsive disorder (OCD), and posttraumatic stress disorder (PTSD) in youth. Ancillary factors in child and adolescent anxiety (e.g., personality, temperament, parenting issues, and comorbid conditions). Psychological, pharmacological, and combined treatments for childhood anxiety disorders. Special populations and emerging areas of interest, including anxiety disorders in the contexts of chronic health problems and developmental disabilities. The Handbook of Child and Adolescent Anxiety Disorders is a must-have reference for researchers, clinicians, and graduate students in psychology, psychiatry, social work and counseling as well as allied professionals in hospitals, community mental health centers, schools, and private practice.